2022
DOI: 10.3168/jds.2021-21176
|View full text |Cite
|
Sign up to set email alerts
|

Predicting methane emission in Canadian Holstein dairy cattle using milk mid-infrared reflectance spectroscopy and other commonly available predictors via artificial neural networks

Abstract: Interest in reducing eructed CH 4 is growing, but measuring CH 4 emissions is expensive and difficult in large populations. In this study, we investigated the effectiveness of milk mid-infrared spectroscopy (MIRS) data to predict CH 4 emission in lactating Canadian Holstein cows. A total of 181 weekly average CH 4 records from 158 Canadian cows and 217 records from 44 Danish cows were used. For each milk spectra record, the corresponding weekly average CH 4 emission (g/d), test-day milk yield (MY, kg/d), fat y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…The use of these tools in breeding programs will allow breeders to produce more milk and solids with a more desirable distribution of specific characteristics over time. Furthermore, it will allow production of milk that has more desirable properties for both manufacturers and consumers, making selection for peripherally associated traits like reduced methane emissions possible (e.g., Shadpour et al, 2022 ).…”
Section: Energy Metabolism Milk Composition Fertility and Sustainabil...mentioning
confidence: 99%
“…The use of these tools in breeding programs will allow breeders to produce more milk and solids with a more desirable distribution of specific characteristics over time. Furthermore, it will allow production of milk that has more desirable properties for both manufacturers and consumers, making selection for peripherally associated traits like reduced methane emissions possible (e.g., Shadpour et al, 2022 ).…”
Section: Energy Metabolism Milk Composition Fertility and Sustainabil...mentioning
confidence: 99%
“…Partial least squares (PLS) is the preferred and most traditional way to correlate MIRS data with milk and animal traits because of its ability to consider covariate and high-dimensional datasets. However, for complex relationships between variables (e.g., nonlinearities and interactions), PLS may not be an ideal treatment [22]. Some MIRS studies on milk have demonstrated that other machine learning algorithms such as random forests (RF), decision trees, and neural networks (NN) are also able to effectively handle milk MIRS data [23].…”
Section: Introductionmentioning
confidence: 99%